2023
DOI: 10.1101/2023.06.06.543780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Spatiotemporal Compartmentalization of Glucose Metabolism Guides Mammalian Gastrulation Progression

Abstract: Gastrulation is considered the sine qua non of embryogenesis, establishing a multidimensional structure and the spatial coordinates upon which all later developmental events transpire. At this time, the embryo adopts a heavy reliance on glucose metabolism to support rapidly accelerating changes in morphology, proliferation, and differentiation. However, it is currently unknown how this conserved metabolic shift maps onto the three-dimensional landscape of the growing embryo and whether it is spatially linked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Recent work investigated the role of glucose metabolism during mouse peri-gastrulation stages using (st)embryos. 51,39 One study showed that during early gastrulation (∼E6.5 - ∼E7.25) mesoderm fate acquisition and maintenance is governed by glucose metabolism via the Hexosamine Biosynthetic Pathway (HBP), but mesoderm migration and lateral expansion requires glycolysis. 51 Complementary work in gastruloids suggested that mannose, but not glycolysis, is crucial for the early induction of T .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work investigated the role of glucose metabolism during mouse peri-gastrulation stages using (st)embryos. 51,39 One study showed that during early gastrulation (∼E6.5 - ∼E7.25) mesoderm fate acquisition and maintenance is governed by glucose metabolism via the Hexosamine Biosynthetic Pathway (HBP), but mesoderm migration and lateral expansion requires glycolysis. 51 Complementary work in gastruloids suggested that mannose, but not glycolysis, is crucial for the early induction of T .…”
Section: Discussionmentioning
confidence: 99%
“…51,39 One study showed that during early gastrulation (∼E6.5 - ∼E7.25) mesoderm fate acquisition and maintenance is governed by glucose metabolism via the Hexosamine Biosynthetic Pathway (HBP), but mesoderm migration and lateral expansion requires glycolysis. 51 Complementary work in gastruloids suggested that mannose, but not glycolysis, is crucial for the early induction of T . 39 While at first glance some of these findings seem at odds with our discoveries, most of the effects we report here relate to later developmental stages (embryo equivalent: ∼E7.5-E9 4 ), during which mesoderm and neural cells are specified from a pool of NMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Together, the results point to a critical role for mannose-dependent glycosylation for proper mesoderm specification in gastruloids [ 36 ]. This in vitro study was complemented by an in vivo dataset, also highlighting the role of glycosylation in mesoderm specification during gastrulation [ 37 ].…”
Section: Why Gastruloids?mentioning
confidence: 99%
“…As various forms of NAD serve as cofactors in various oxidoreductive reactions, their relative fluorescence intensity can used as a readout of a particular metabolic state of cells within a tissue. Recently, it has been shown a posterior–anterior gradient of NAD(P)H in the gastrulating mouse embryo [ 37 ]. One limitation is such cofactors are produced and utilised in a wide range of pathways and again this makes it difficult to gain a spatial information on the actual metabolic state of cell in situ .…”
Section: Future Directions For the Fieldmentioning
confidence: 99%